Peripheral facial paralysis: the role of physical medicine and rehabilitation. - Matos, Catarina (2011)
Peripheral facial paralysis (PFP) is a consequence of the peripheral neuronal lesion of the facial nerve (FN). It can be either primary (Bell`s Palsy) or secondary. The classical clinical presentation typically involves both stages of the hemiface. However, there may be other symptoms (ex. xerophthalmia, hyperacusis, phonation and deglutition changes) that one should recall. Clinical evaluation includes rigorous muscle tonus and sensibility search in the FN territory. Some useful instruments allow better objectivity in the patients' evaluation (House-Brackmann System, Facial Grading System, Functional Evaluation). There are clear referral criteria to Physical Medicine and Rehabilitation. Treatment of Bell`s Palsy may include pharmacotherapy, neuromuscular training (NMT), physical methods and surgery. In the NMT field the several treatment techniques are systematized. Therapeutic strategies should be problem-oriented and adjusted to the patient's symptoms and signs. Physical methods are reviewed. In about 15-20 % of patients permanent sequelae subside after 3 months of evolution. PFP is commonly a multidisciplinary condition. Therefore, it is important to review strategies that Physical Medicine and Rehabilitation may offer.